Estudo das propriedades mecânicas do aço ao boro 50B35 com diferentes tamanhos de grãos - Santos, Ricardo Jonatas Cerutti (Universidade Federal de São Carlos, 2015)
Boron steel has excellent hardenability due to the addition of small quantities of boron. Boron atoms reduces the nucleation rate of ferrite and bainite [1]. It is known that austenitizing temperature and time and cooling rate are the main factors responsible for hardenability loss on boron steel. The austenitizing temperature relates to the boroncarbide precipitation that happens during the heat treatment. The boroncarbide precipitation is related to the austenitization temperature during heat treatment. The austenitization time defines the grain size condition that during cooling may or not transform into martensite which is decisive to the final properties. This study was conducted to simulate different grain sizes for a given boron steel (50B35), keeping the austenitizing temperature and the cooling rate constant, so that the only variable was the grain size. Therefore, the objective of this study was to understand the grain size effect on boron steel by keeping or not the hardenability effect and characterize the non-martensitic phases like ferrite and bainite and its consequences on the mechanical properties. It was observed fully martensitic structure for finer grain size (ASTM N.5), loss of hardenability characterized by the presence of bainite, for intermediate grain size (ASTM N.4) and hardenability recovery, by increasing the martensite percentage for bigger grains size (ASTM N.3). To conclude, there is a limit for the boron atom to lead the hardenability effect, from a given grain size the effect of hardenability is driven by the grain size itself, like in a normal carbon steel. There was loss on the ductility when increasing the austenitic grain size. For intermediate grain size both yield and tensile strength were reduced and it can be associated to the presence of bainite. For bigger grain size, both yield and tensile strength were recovered to levels near those observed at that for smaller grain size but without recovering ductility.
Study of mechanical properties of boron steel 50b35 for different grain sizes
Keywords: Tratamento térmicos; Aços ao boro; Tamanho de grão; Propriedades mecânicas; Temperabilidade; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA